2019
DOI: 10.1051/bioconf/20191202020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the extent of ethanol removal on the volatile compounds of a Chardonnay wine dealcoholized by vacuum distillation

Abstract: “Beverages obtained from the partial dealcoholization of wine” are those drinks whose final alcoholic degree after dealcoholization is lower than that of a wine and higher than or equal to 0.5% v/v. When the total alcoholic degree is lower than 0.5% v/v the denomination is “Beverages obtained from the dealcoholization of wine”. The practices to be authorized for the production of these drinks with the dealcoholized wine fractions are currently being studied at OIV. The characterization of the composition of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Moreover, Liguori et al [16] observed no change in 1-hexanol concentration in wine fractions dealcoholized by 6.5% alcohol using osmotic distillation, while in this study the concentration of 1-hexanol was significantly reduced in all wines after dealcoholization by RO and VD. In agreement with our results, other studies found losses of 5% to 15% 1-hexanol in red wines dealcoholized by 2.5% alcohol by RO-EP [50], 84% losses in Chardonnay wine dealcoholized by 10.61% v/v ethanol using vacuum distillation [14], 66% to 71% losses in wines (Langhe Rosè, Barbera red, and Verduno Pelaverga wines) dealcoholized at 5% alcohol by RO and VD [13], 17% to 35% losses in white and red wines dealcoholized by 4% alcohol by a membrane contactor [74], and 28% to 38% losses in Aglianico wines dealcoholized by 5% alcohol with an osmotic distillation method [8]. In the later studies, losses of 1-hexanol increased with the degree of dealcoholization [8,74].…”
Section: Higher Alcoholssupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, Liguori et al [16] observed no change in 1-hexanol concentration in wine fractions dealcoholized by 6.5% alcohol using osmotic distillation, while in this study the concentration of 1-hexanol was significantly reduced in all wines after dealcoholization by RO and VD. In agreement with our results, other studies found losses of 5% to 15% 1-hexanol in red wines dealcoholized by 2.5% alcohol by RO-EP [50], 84% losses in Chardonnay wine dealcoholized by 10.61% v/v ethanol using vacuum distillation [14], 66% to 71% losses in wines (Langhe Rosè, Barbera red, and Verduno Pelaverga wines) dealcoholized at 5% alcohol by RO and VD [13], 17% to 35% losses in white and red wines dealcoholized by 4% alcohol by a membrane contactor [74], and 28% to 38% losses in Aglianico wines dealcoholized by 5% alcohol with an osmotic distillation method [8]. In the later studies, losses of 1-hexanol increased with the degree of dealcoholization [8,74].…”
Section: Higher Alcoholssupporting
confidence: 93%
“…Partial dealcoholization (up to 2% v/v) has become another practice in oenology [11]. Dealcoholization methods generate changes in the organoleptic properties of wines (even membrane methods cause compositional changes) that go beyond alcohol extraction [12][13][14][15][16][17]. This makes the resulting wines have a different flavor and aroma.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique reduces the risk of flavor loss while effectively lowering alcohol content. Winemakers appreciate vacuum distillation for its ability to modify the wine's composition without compromising its sensory attributes [155,156].…”
Section: Improving Port Wine Production and Its Effect On Vinegarmentioning
confidence: 99%